2020
DOI: 10.1063/1.5132626
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-controlled magnetic anisotropy in an ultrathin Ir-doped Fe layer with a CoFe termination layer

Abstract: We investigated the voltage-controlled magnetic anisotropy (VCMA) in an ultrathin Ir-doped Fe layer with a CoxFe1−x termination layer. The VCMA effect depends on the concentration of the CoxFe1−x alloy, and a large VCMA coefficient, as high as −350 fJ/Vm, was obtained with a Co-rich termination layer. First principles calculations revealed that the increased VCMA effect is due not only to the added Co atoms but also to the Fe and Ir atoms adjacent to the Co atoms. Interface engineering using CoFe termination i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 41 publications
1
44
0
Order By: Relevance
“…Recently, Nozaki et al demonstrated a significant enhancement in the VCMA effect, as high as 350 fJ/Vm, via engineering of the FM/oxide interface in an ultrathin Ir-doped Fe/MgO structures with a CoFe termination layer. 45 Employing an ionic mechanism to control the PMA could potentially result in even stronger modulation of the damping and possibly also non-volatile storage of different damping values. 46 Further improvement in the damping modulation should also be possible via optimizing the device layout.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Nozaki et al demonstrated a significant enhancement in the VCMA effect, as high as 350 fJ/Vm, via engineering of the FM/oxide interface in an ultrathin Ir-doped Fe/MgO structures with a CoFe termination layer. 45 Employing an ionic mechanism to control the PMA could potentially result in even stronger modulation of the damping and possibly also non-volatile storage of different damping values. 46 Further improvement in the damping modulation should also be possible via optimizing the device layout.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one can achieve I eff = 170 μA using the standard material in SOT MRAM technology, such as tungsten, with θ SH = −0.45 [34]. Correspondingly, ξ = 300 fJ/Vm is needed, which can be implemented by appropriate interface engineering [35]. For comparison, these values are much more relaxed than the requirements for SOT MRAM (|θ SH | > 1.6) and for VCMA MRAM (ξ > 800 fJ/Vm, considering t MgO = 1.5 nm at μ 0 H x = 0 mT) of the same .…”
Section: A Device-scaling Criteriamentioning
confidence: 99%
“…The voltage control of magnetic anisotropy (VCMA) effect 2 , 3 and VCMA-induced precessional magnetization switching 4 , 5 , which are the core technologies of the voltage-controlled MRAM, have been extensively investigated, especially for bcc-Fe/MgO-based systems 6 9 , because of the high compatibility with MRAM. Regarding the purely-electronic VCMA effect, a VCMA coefficient of approximately 350 fJ/Vm has been realized for the epitaxial Cr/Fe/Ir/FeCo/MgO structure by precise control of the film structure using the molecular beam epitaxy (MBE) technique 10 , 11 . However, further enhancement of the VCMA coefficient is demanded.…”
mentioning
confidence: 99%